Microbial Pigments as Innovative Therapeutic Agents for Combating Infections and ‎Advancing Cancer Treatment - Gudepu, Renuka (International Journal of Biological Research, 2025)
Microbial pigments have gained significant attention as promising therapeutic agents due to their ‎diverse bioactive properties, including antibacterial, anticancer, cytotoxic, and antioxidant ‎activities. These natural pigments, produced by bacteria, offer immense potential in both ‎medicinal and industrial applications. In this study, a thorough literature review was conducted ‎to explore the therapeutic significance of bacterial pigments, particularly their role in combating ‎infections and advancing cancer treatment. The pigment was characterized using UV-visible ‎spectroscopy, with absorption spectra ranging from 220 to 250 nm. Additionally, Fourier-transform infrared (FTIR) spectroscopy of strain BJZ10 identified functional groups associated ‎with alcohols, esters, sulfate, alkanes, and alkyls, confirming the structural complexity of the ‎pigment. The antibacterial efficacy of the pigment was evaluated using both Gram-positive ‎‎(Bacillus cereus) and Gram-negative (Escherichia coli) bacteria, demonstrating significant ‎antimicrobial activity. Notably, this study identified a brown pigment produced by Streptomyces ‎sp. strain BJZ10, which exhibited strong antibacterial properties. Given these findings, microbial ‎pigments hold substantial promise for therapeutic applications, particularly in antimicrobial and ‎anticancer strategies. This paper discusses the potential biomedical applications of microbial ‎pigments, emphasizing their role as next-generation therapeutic agents in treating infections and ‎combating cancer‎.